Checklist of net-winged beetles (Coleoptera: Lycidae) from Mexico - Pérez-Hernández, Cisteil X.; Zaragoza-Caballero, Santiago; Romo-Galicia, Alberto (Zootaxa, 2019)
A checklist, distribution records, and the updated nomenclature for Mexican Lycidae are presented here. Two subfamilies, 7 tribes, 24 genera, 2 subgenera and 168 valid species of Lycidae (Coleoptera: Elateroidea) taxa were recorded from Mexico, including 111 (66%) endemic species. For each species, synonyms used in Mexico and geographical distribution in Mexican states were provided. The highest species richness was recorded in Veracruz, Chiapas and Oaxaca, while Aguascalientes and the Yucatan Peninsula states had very few records of Lycidae species probably due to the lack of fieldwork. In the Nearctic region, Lycidae diversity comprised 4 tribes, 10 genera and 27 species; in Mexican transition zone, 5 tribes, 17 genera and 100 species; and in Neotropical region, 7 tribes, 19 genera and 94 species. The highest species richness of Lycidae was recorded in the Veracruzan, Transmexican Volcanic Belt and Chiapas Highlands provinces. Although there has been a relevant rise in taxonomical work concerning Mexican lycid fauna in the last two decades, it is still necessary to continue in systematic, ecological, and biogeographical studies of the family in Mexico, especially in scarcely studied regions.